Degradation Study of Ketorolactromethamine by a Validated UPLC Method - Uddin, Mohammad Nasir; Al-Amin, Md.; Haque Mijan, Md. Nazmul; Das, Suman (Indonesian Journal of Pharmaceutical Science and Technology, 2019)
UPLC stability indicating method was developed for determining ketorolac tromethamine in its degradation study at different conditions. An isocratic mobile phase composition of 60:10:30 (v/v) containing CH3OH, CH3CN and 5mM NaH2PO4 and C18 column were used at a flow rate of 0.20 mL min-1. Satisfactory retention time was found 2.13Â±0.05 min at 320 nm when monitored by DAD detector. Forced degradation studies of ketorolac tromethamine was also performed at the following conditions: acid and basic hydrolysis, heat (50-70Â°C for 1 hr), photolytic (UV and sunlight for up to 3 hr), oxidation (3% hydrogen peroxide for 1 hr). Forced degradation study revealed that ketorolac degraded significantly under thermal conditions. In 1N acid and base hydrolysis, degradation was moderately significant and comparable. It was degraded marginally in 0.1N acid-base hydrolysis which was comparable to oxidative conditions. But in photolytic condition ketorolac shows insignificant degradation. Method was also applied to pharmaceutical formulation.Keywords: UPLC, Ketorolac tromethamine, pharmaceutical formulation, Forced degradation